"Teacher education is a good choice, but I don't want to teach in schools." An analysis of university students' career decision making. Issue 4 (8th August 2021) - Suryani, Anne; George, Sindu
ABSTRACT: This paper reports qualitative findings from a large study on Indonesian teacher education students' career aspirations. The participants were 133 final-year undergraduate students who entered teacher education programmes with no intentions to teach in schools or had intentions to teach only for a short period upon graduation before pursuing another career. Their motivations to choose teacher education programmes are analysed from the perspectives of the social learning theory of career decision making. The most popular reasons were good reputation of the universities, convenient campus location, and comparatively low tuition fees for the programme. Provision of scholarship was also an attraction. Career possibilities outside teaching was another key reason for entering the programme. While a few students perceived teacher education as a stepping stone to pursue another career, some did not have any specific plan but followed their parents' advice and friends' choice of study. Participants' perceptions about teacher education programmes and teaching are discussed along with implications.